2018
DOI: 10.3389/fpsyg.2018.00818
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acoustic Distance and Sociolinguistic Knowledge in Dialect Identification

Abstract: Listeners are able to quite accurately distinguish between different dialects of their native language, but little is known about the process of dialect identification and the phonetic cues listeners use to identify someone’s regional origin. This study examines how different segments, acoustic between-dialect distance, and the listeners’ knowledge about a dialect contribute to this process. Native speakers of Grison and Zurich German were asked to categorise isolated words spoken by eight speakers of Grison a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…The presented GAM therefore successfully examined the effects of listener-related factors on listeners' accent-recognition errors. The results parallel the findings of prior studies investigating levels of categorization accuracy for speaker origin (e.g., Bent et al, 2016;Gnevsheva, 2018;McKenzie, 2019;Preston, 1999;Ruch, 2018;Watanabe, 2017). Although adult listeners were shown to be generally able to identify speakers' regional origins with reasonable accuracy, their accent-recognition patterns were imperfect.…”
Section: Key Findings From the Present Studysupporting
confidence: 78%
See 1 more Smart Citation
“…The presented GAM therefore successfully examined the effects of listener-related factors on listeners' accent-recognition errors. The results parallel the findings of prior studies investigating levels of categorization accuracy for speaker origin (e.g., Bent et al, 2016;Gnevsheva, 2018;McKenzie, 2019;Preston, 1999;Ruch, 2018;Watanabe, 2017). Although adult listeners were shown to be generally able to identify speakers' regional origins with reasonable accuracy, their accent-recognition patterns were imperfect.…”
Section: Key Findings From the Present Studysupporting
confidence: 78%
“…These speakers might therefore be exposed to less linguistic variability, making them less familiar with other accents and thus poorer listeners. Ruch (2018), in contrast, raised the hypothesis that urban speakers are more in contact with different varieties on a daily basis than rural speakers and might therefore be more sensitive to variability. In order to test these hypotheses in future studies, it would make sense to include rurality versus urbanity as a listener factor, together with a measure of listeners' mobility profiles.…”
Section: Social and Geographical Factorsmentioning
confidence: 99%
“…Moreover, the nonnative listeners' mother tongues (i.e. Italian and Persian) have crucial differences in the vocalic and consonantal inventory as well in their rhythmic organization (Majidi and Ternes, 1999;Loporcaro and Bertinetto, 2005;Fleischer and Schmid, 2006;Leemann et al 2012;Ruch, 2018) which presumably made it hard to benefit from the first language to distinguish speaker-from dialect-specific features. Conversely, the group of Zurich German listeners had a clear advantage in voice discrimination since they could process the full set of linguistic information available in the stimuli, and thus be sensitive to subtle differences in segmental and prosodic information.…”
Section: Discussionmentioning
confidence: 99%
“…We selected ZHG listeners in this study for dialect familiarity reasons. Previous research on the role of sociolinguistic knowledge and language distance in dialect identification has shown that (1) ZHG listeners are more sensitive to dialectal differences and performed more accurately than GRG listeners, and that (2) Swiss German subjects have a shared knowledge about the dialect specific features of GRG and perceive ZHG as a more neutral dialect (Ruch, 2018). To ensure that listeners have comparable socio-linguistic background, after the speaker discrimination experiment, they filled out a questionnaire about their linguistic and dialectal background (e. g. contexts and frequency of exposure to/use of Zurich German), familiarity with Swiss German dialects and knowledge of second languages.…”
Section: [Figure 1_2122 Near Here]mentioning
confidence: 99%
“…As there is ample evidence of dialect levelling of traditional Andalusian features in syllable-onset position in favor of supra-local features throughout Andalucía (Hernández Campoy & Villena Ponsoda, 2009;Moya Corral, 2018b;Villena Ponsoda & Vida Castro, 2020; inter alia), future studies should look to conduct perception studies of these variants in order to shed light into the social motivation for such dialect levelling of traditional features. Additionally, more studies should not only analyze specific communities, but compare specific communities within larger regions (Ruch, 2018a, Ruch, 2018b as well as nearby communities (Watson & Clark, 2013) in order to find more nuanced evaluations of linguistic variables that would be overlooked in larger regional labels such as Andalusians, Pennsylvanians, Texans, or Southerners. In conclusion, the current study has demonstrated that while the communities of Huelva and Lepe share similar language attitudes in evaluating the supra-local Castilian feature [tʃ] as more overtly prestigious than the traditional Andalusian feature [ʃ], there are nuanced differences in attitudes between the two communities due to their unique historical and socioeconomic developments.…”
Section: Discussionmentioning
confidence: 99%